(untitled) (Revista Electrónica REDINE, 2026)
Early childhood education, particularly in its maternal stage, represents the foundation for a child’s holistic development during the first three years of life. This article analyzes the convergence between the theoretical frameworks that underpin this level and the pedagogical practices implemented in Venezuelan institutions. A historical-analytical documentary investigation was applied, based on the review of primary and secondary sources. For the formation of the study corpus, inclusion criteria were applied (National and international legal and regulatory documents. Statistical data on institutional coverage in Venezuela (1977-2025 in addition to previous investigations that address the physical, human and pedagogical components as transversal elements that redefine praxis and dedogmatize theory). Sources lacking academic peer review, documents, and studies that did not have a direct connection to the Venezuelan socio-educational context were excluded. The findings reveal critical tensions between the stated model and the model in use, identifying weaknesses in specialized teacher training, the relevance of planning, and institutional coverage. It is concluded that there is a disconnect between theoretical postulates and classroom reality. Finally, it is emphasized that strengthening the maternal stage in Venezuela requires professionalizing human resources and implementing didactic management that coincides with the systematization of experiences in this crucial stage for the comprehensive development of the infant.